Role of Per1 and the mineralocorticoid receptor in the coordinate regulation of αENaC in renal cortical collecting duct cells - Richards, Jacob; Jeffers, Lauren A.; All, Sean C.; Cheng, Kit-Yan; Gumz, Michelle L. (Frontiers in Physiology, 2013)
Renal function and blood pressure exhibit a circadian pattern of variation, but the molecular mechanism underlying this circadian regulation is not fully understood. We have previously shown that the circadian clock protein Per1 positively regulates the basal and aldosterone-mediated expression of the alpha subunit of the renal epithelial sodium channel (αENaC). The mechanism of this regulation has not been determined however. To further elucidate the mechanism of Mineralocorticoid Receptor (MR) and Per1 action, site-directed mutagenesis, DNA pull-down assays and chromatin immunoprecipitation methods were used to investigate the coordinate regulation of αENaC by Per1 and MR. Mutation of two circadian response E-boxes in the human αENaC promoter abolished both basal and aldosterone-mediated promoter activity. DNA pull down assays demonstrated the interaction of both MR and Per1 with the E-boxes from the αENaC promoter. These observations were corroborated by chromatin immunopreciptation experiments showing increased occupancy of MR and Per1 on an E-box of the αENaC promoter in the presence of aldosterone. This is the first report of an aldosterone-mediated increase in Per1 on a target gene promoter. Taken together, these results demonstrate the novel finding that Per1 and MR mediate the aldosterone response of αENaC through DNA/protein interaction in renal collecting duct cells.